A Narrative Inquiry of English Graduate Students’ Experiences in Writing for Publication - Pradhita Ramadhani; Endang Fauziati; Suparno Suparno (STAI Hubbulwathan Duri, 2021)
Academic writing in higher education mainly focuses on writing for publication. The success of writing for publication depends on the learners’ ability to access, understand the relevant references, evaluate, and synthesise the ideas, opinions, and sentences to make their academic pattern. Viewed from prior studies, it seems that many EFL learners have faced various problems in writing their academic papers, specifically writing for publication. To respond to this issue, this narrative inquiry aims to investigate (1) how learners acquire their knowledge in writing for publication, (2) the difficulties they face in writing for publication, and (3) how they face those difficulties. This present study intended to dig up the experiences of two graduate students of English Education major in writing for publication. Semi-structured interviews were used to collect the data. Then, the data were analyzed using thematic analysis. This study shows that the participants acquired knowledge and experiences from various sources that were useful for writing their academic papers. Surprisingly, the various difficulties they faced motivated them to learn more and improve their writing skills for publication. Pedagogical and future research implications are further discussed.